Strategies for improving the protection of weapons and military equipment - Melnyk, Boris; Veretnov, Andriy; Novikova, Iryna (Social Development and Security, 2023)
Purpose: there are directions strategies for improving the protection of weapons and military equipment. Method: for the purpose of the research of development and the primary design features of armored combat vehicles, international technical assistance aimed at ensuring protection against weapons of destruction. The classification of armored combat vehicles by weight and dimensions and the peculiarities of approaches to increasing their level of protection are outlined. The experience of the Republic of South Africa, NATO member states, the Russian Federation, and the defense industry of Ukraine in developing armored combat vehicles with an increased level of protection is examined. Findings: the article explores analyze the trends in the development of weaponry and military equipment received as part of international technical assistance, specifically focusing on ways to enhance their protection against means of destruction. Papertype: theoretical.